Assessing gamification-based LMS for EFL students: A self-directed learning framework - Slamet, Joko; Basthomi, Yazid (Studies in Linguistics, Culture and FLT (Online), 2024)
The efficacy of gamification-based Learning Management Systems (LMS) in facilitating English as a Foreign Language (EFL) learning is an area of growing interest. However, a critical gap exists in comprehensively understanding how these platforms influence self-directed learning (SDL) among EFL students, particularly regarding self-management, self-motivation, and self-control. To address this lacuna, this study employs a survey design involving 50 EFL undergraduate students from STKIP PGRI Sidoarjo, a private university, in Indonesia. Grounded in Garrison’s SDL Framework, the research evaluates the impact of gamification on SDL dimensions within the LMS milieu. The data were collected through a questionnaire for quantitative analysis and interviews for qualitative insights. Findings unveil a nuanced landscape: while gamification initially boosts engagement and motivation, sustained self-management and control pose challenges. Implications underscore the imperative for tailored interventions to fortify SDL competencies within gamified environments. Recommendations advocate for the integration of personalized feedback mechanisms and collaborative features to scaffold EFL students’ SDL skills amidst gamified platforms.